Visualizing membrane microdomains by Laurdan 2-photon microscopy. - Gaus, K; Zech, T; Harder, T (2006)
Lateral segregation of cell membrane components gives rise to microdomains with a different structure within the membrane. Most prominently, lipid rafts are defined as domains in liquid ordered phase whereas surrounding membranes are more fluid. Here we review a 2-photon fluorescence microscopy approach, which allows the visualization of membrane fluidity. The fluorescent probe Laurdan exhibits a blue shift in emission with increasing membrane condensation caused by an alteration in the dipole moment of the probe as a consequence of exclusion of water molecules from the lipid bilayer. The quantification of membrane order is achieved by the Generalized Polarization (GP) values, which are defined as normalized intensity ratios of two emission channels. GP images are therefore not biased by probe concentrations and membrane ruffles. Furthermore, Laurdan reports membrane structure independently from the lipid and protein cargo of the membrane domains. We give examples where Laurdan microscopy was instrumental in quantifying the formation of condensed membrane domains and their cellular requirements. Moreover we discuss how microdomains identified by Laurdan microscopy are consistent with domains identified by other methodologies and put GP images in the context of current raft hypotheses.